Predictive-like distribution mapping using Google Earth: Reassessment of the distribution of the bromeligenous frog, Scinax v-signatus (Anura: Hylidae) - Da Silva, Helio Ricardo; Alves-Silva, Ricardo (Zootaxa, 2013)
The hylid frog Scinax perpusillus species group comprises 13 species that share, in addition to a few morphological features, reproduction that occurs exclusively associated with bromeliads. Among the species in the group, Scinax v-signatus (Lutz, 1968) is one of the few with a relatively large geographic distribution, occurring in association with bromeliads growing on granitic outcrops above 800 m along the Serra dos Órgãos (a local designation of Serra do Mar) in the Atlantic forest, State of Rio de Janeiro. Here we demonstrate that previous assessment of the distribution of this species was overestimated, and reevaluate the available data on its occurrence. The distributional data analyzed was based on three levels of evidence. First, we assessed the distribution of the bromeliad, Alcantarea imperialis (Carrière) Harms, which is used by S. v-signatus at the type locality. We plotted potential occurrence data for this plant using Google Earth (GE) by visually inspecting GE images in search of indications of granitic outcrops where groups and large individual bromeliads could be identified. Second, we plotted the distribution of these plants and that of the frog based on locality data taken from the literature and voucher specimens in natural history collections and checked for congruence between these sets of data. Third, as a second test of accuracy of this methodology we visited four new localities indicated by the bromeliad-occurrence GE prediction map and searched for the occurrence of both the frog and the bromeliad. This simple process has proven efficient and accurate in finding new collecting sites and determining the distribution of the two involved taxa. We discuss this and other possibilities of using Google Earth as a tool for mapping and discovering the distribution of organisms and habitats. Furthermore, this study has shed light on a more accurate and realistic estimate of the distribution of Scinax v-signatus with implications for the assessment of its conservation status.